Effects of Lactobacillus acidophilus and tussah immunoreactive substances on disease resistance of sea cucumber (Apostichopus japonicus) against Vibrio splendidus. (29th April 2021) - Wang, Xuda; Jiang, Jingwei; Guan, Xiaoyan; Zhao, Zelong; Dong, Ying; Wang, Jian; Li, Shilei; Jiang, Bei; Liu, Guiying; Sun, Hongjuan; Gao, Shan; Jiang, Pingzhe; et al.
Abstract: Effects of dietary Lactobacillus acidophilus and tussah immunoreactive substances (TIS) on disease resistance of sea cucumber ( Apostichopus japonicus ) against Vibrio splendidus were investigated. Sea cucumbers were fed with a basal diet in the control group (CK group) or were supplemented with L . acidophilus (L group), TIS (T group) or both (LT group). The challenge test with V . splendidus was conducted after the feeding trial. The cumulative mortality rate in the LT group was significantly lower, while the highest mortality occurred in the control group. The LT group showed better digestive and immune parameters compared with the other treatments. Dietary L . acidophilus and TIS in combination could effectively enhance digestive function and food uptake, depress oxidative damage and improve the organismal defence capability. Regarding gut microbiota profiles, the LT group was more capable of inhibiting potentially opportunistic pathogens and regulating intestinal flora balance compared with the other groups. The administration of L . acidophilus and TIS in the diet could effectively improve disease resistance against V . splendidus of sea cucumbers by improving the immune and digestive enzyme activities and modulating intestinal microflora, signalling a potential role in the development and production of aquatic feed. Abstract :